Nonlinear time series models in empirical finance - Franses, Philip Hans, 1963- (Cambridge University Press, 2000)
The most up-to-date and accessible guide to one of the fastest growing areas in financial analysis by one of Europes's leading teaching and researching teams. This classroom-tested advanced undergraduate and graduate textbook provides an in-depth treatment of non-linear models, including regime-switching and artificial neural networks.